İnitsiyal. Çasopis za Srednyovekovne Studiye (Beograd [Belgrad])
c.
Keywords: “Initial is a multidisciplinary review of medieval studies intended for publishing contributions from all academic fields pertaining to the area of Southeastern Europe and the Mediterranean in the Middle Ages. This includes not only papers discussing new theoretical approaches in medieval studies or interpreting so-called „major issues“, but also those focusing on narrower, more specialized fields of research. However, with regard to the character of the review authors should craft their material to appeal to a wider audience of medievalists, providing the necessary context to readers who may not be so well-versed in the particular subject. Editions and translations of medieval sources may also be submitted for publication, especially if they are an essential component of a wider study...“ -- Yayıncı.